Anatomical pathways for auditory memory II: information from rostral superior temporal gyrus to dorsolateral temporal pole and medial temporal cortex - Muñoz-López, M.; Insausti, R.; Mohedano-Moriano, A.; Mishkin, M.; Saunders, R. C. (Frontiers in Neuroscience, 2015)
Auditory recognition memory in non-human primates differs from recognition memory in other sensory systems. Monkeys learn the rule for visual and tactile delayed matching-to-sample within a few sessions, and then show one-trial recognition memory lasting 10-20 minutes. In contrast, monkeys require hundreds of sessions to master the rule for auditory recognition, and then show retention lasting no longer than 30-40 seconds. Moreover, unlike the severe effects of rhinal lesions on visual memory, such lesions have no effect on the monkeys’ auditory memory performance. It is possible, therefore, that the anatomical pathways differ. Long-term visual recognition memory requires anatomical connections from the visual association area TE with areas 35 and 36 of the perirhinal cortex (PRC). We examined whether there is a similar anatomical route for auditory processing, or that poor auditory recognition memory may reflect the lack of such a pathway. Our hypothesis is that an auditory pathway for recognition memory originates in the higher order processing areas of the rostral superior temporal gyrus (rSTG), and then connects via the dorsolateral temporal pole to access the rhinal cortex of the medial temporal lobe. To test this, we placed retrograde (3% FB and 2% DY) and anterograde (10% BDA 10,000 MW) tracer injections in rSTG and the dorsolateral area 38DL of the temporal pole. Results showed that area 38DL receives dense projections from auditory association areas Ts1, TAa, TPO of the rSTG, from the rostral parabelt and, to a lesser extent, from areas Ts2-3 and PGa. In turn, area 38DL projects densely to area 35 of PRC, entorhinal cortex, and to areas TH/TF of the posterior parahippocampal cortex. Significantly, this projection avoids most of area 36r/c of PRC. This anatomical arrangement may contribute to our understanding of the poor auditory memory of rhesus monkeys.